Neuromuscular electrical stimulation‐assisted gait increases muscle strength and volume in children with unilateral spastic cerebral palsy. (11th November 2015) - Pool, Dayna; Elliott, Catherine; Bear, Natasha; Donnelly, Cyril J; Davis, Caroline; Stannage, Katherine; Valentine, Jane
Abstract : Aim: To determine if neuromuscular electrical stimulation (NMES) applied to the ankle dorsiflexors during gait improves muscle volume and strength in children with unilateral spastic cerebral palsy (CP). Method: Thirty‐two children (15 females, 17 males; mean age 10y 8mo, age range 5y 5mo–18y 1mo) with unilateral spastic CP and a Gross Motor Function Classification System of level I or level II were randomly assigned to either the 8‐week daily NMES treatment group or control group (usual or conventional treatments). Outcomes at week 8 (post‐NMES) and week 14 (carryover) included magnetic resonance imaging for muscle volumes (tibialis anterior, anterior compartment, and gastrocnemius), strength (hand‐held dynamometry for isometric dorsiflexion strength and heel raises for functional strength), and clinical measures for lower limb selective motor control. Results: At week 8, the treatment group demonstrated significantly ( p <0.05) increased muscle volumes for tibialis anterior, anterior compartment, medial and lateral gastrocnemius, and dorsiflexion strength not only when compared to their baseline values but also when compared to the control group at week 8. At week 14, both tibialis anterior and lateral gastrocnemius volumes in the treatment group remained significantly increased when compared to their baseline values. However, only lateral gastrocnemius volumes had significantly greater values when compared to the control group at week 14. There were no between group differences in the clinical measures for lower limb selective motor control at week 8 and 14. Interpretation: Eight weeks of daily NMES‐assisted gait increases muscle volume and strength of the stimulated ankle dorsiflexors in children with unilateral spastic CP. These changes are use‐dependent and do not carry over after the 8‐week treatment period. Gastrocnemius volume also increased post‐treatment with carryover at week 14. What this paper adds: Neuromuscular electrical stimulation (NMES)‐assisted gait is a viable treatment option for children with unilateral spastic cerebral palsy to increase the muscle strength and volume of the stimulated ankle dorsiflexors. Gastrocnemius muscle volume also increases post‐treatment with carryover. This suggests that NMES‐assisted gait could be a viable supplement to targeted strength training and serial botulinum toxin treatments. This article is commented on by Dayanidhi on pages432–433 of this issue.